Effect of FOLFOX6 chemotherapy on serum VEGF expression in advanced colorectal cancer patients - Ying,Kong (2019)
SUMMARY OBJECTIVE: To explore the effect of FOLFOX6 chemotherapy on serum vascular endothelial growth factor (VEGF) expression in advanced colorectal cancer patients. METHODS: A retrospective analysis of 81 patients with advanced colorectal cancer who visited our hospital from March 2014 to February 2016 was performed. All the patients were treated with FOLFOX6 chemotherapy. On day 1, patients received oxaliplatin 100 mg/m2 ivgtt (2h), calcium folinate 200 mg/m2 ivgtt (2h), 5 fluorouracil 400 mg/m2 iv bolus and 5 fluorouracil 2500 mg/m2 ivgtt (5h). The treatment course was 2 weeks, and 4 treatment courses were required. The changes in the levels of VEGF and CRP and quality of life before and after 4 courses of chemotherapy were observed and therapeutic effects and adverse reactions after chemotherapy were evaluated. RESULTS: After treatment, the total efficiency of chemotherapy was 82.72% (67/81) with 24 cases in complete remission, 25 cases in partial response, 18 cases in stable disease and 14 cases in progressive disease. The levels of CRP and VEGF after the treatment were significantly lower than those before treatment (5.69±0.77) mg/L vs. (7.99±1.36) mg/L; (443.26±21.55) pg/mL vs. (542.83±20.44) pg/mL] (P<0.05). The KPS grade after treatment was significantly higher than that before treatment (57.84±4.6) point vs. (50.99±3.73) point] (P<0.05). Among them, 3 cases developed a rash, 5 cases experienced hair loss, and 9 cases developed nausea and vomiting. CONCLUSION: FOLFOX6 chemotherapy can decrease serum VEGF expression in patients with advanced colorectal cancer and enhance the curative effect with high safety, which is good for the improvement of patients' survival.